Games and data capture culture: play in the era of accelerated neoliberalism. (July 2022) - Tulloch, Rowan; Johnson, Craig
The last decade has seen the rise of data capture culture. This culture has been most visible, and widely analysed, within the realm of social media; but it is not unique to that form. This article reconceptualises video games as apparatuses for data capture. We situate games within a broader economic and cultural shift towards a new 'accelerated' form of neoliberalism where individual choice and agency are pre-filtered and personalised by algorithms based on user data history. Through a survey of the changing role of data in video gaming, this article critically maps a new paradigm for a reimagined games industry driven by a logic of data capture. Gaming promises a unique opportunity for data capture capitalists to mine and commodify player preferences, behaviours and instinctual responses. Arguing that play is a process of uncovering hidden logics, we offer a framework for resisting the data capture hegemony. This is not simply a discussion of gaming, rather this is an attempt to outline the conditions of possibility for a critique of globalised digital culture in which populations are profiled, processed and punished by hidden algorithms of the market that are optimised to construct and reward accelerated performances of neoliberal subjectivity.